2017
DOI: 10.3892/etm.2017.5294
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the α‑tomatine‑directed apoptosis in human malignant glioblastoma cell lines A172 and U‑118 MG

Abstract: Abstract. In the present study, the molecular mechanisms involved in the α-tomatine-induced apoptosis in human glioblastoma cell lines A172 and U-118 MG were investigated. Wright staining and ApopTag assays were conducted to confirm the apoptosis induced by α-tomatine treatment. Fura-2 assay determined an enhancement in free Ca 2+ intracellularly, indicating the occurrence of Ca 2+ -dependent apoptosis induction. Western blot experiments were also performed to predict the apoptosis by measuring the changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Apoptosis is regulated by key regulatory proteins of the Bcl-2 family. Most Bcl-2 family proteins play a role at the mitochondrial level, and excessive apoptosis caused by abnormal changes in the levels of Bcl-2 proteins is a key step in tumor progression [ 24 , 25 ]. Up-regulation of Bcl-2 gene expression is conducive to the inhibition of apoptosis and anti-apoptotic effect [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is regulated by key regulatory proteins of the Bcl-2 family. Most Bcl-2 family proteins play a role at the mitochondrial level, and excessive apoptosis caused by abnormal changes in the levels of Bcl-2 proteins is a key step in tumor progression [ 24 , 25 ]. Up-regulation of Bcl-2 gene expression is conducive to the inhibition of apoptosis and anti-apoptotic effect [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that α-tomatine inhibits the growth of various human cancer cell lines within 1–48 h in a wide range of concentrations [ 20 , 21 , 22 , 23 , 24 , 25 ]. Our results show that commercial tomatine inhibited both the cell invasion and cell viability of BRAFwt and V600 BRAF metastatic melanoma cells within the range of 0.5–1 μM (expressed as α-tomatine concentration) after 24 h treatment and highlight a previously unknown ability of the bioactive compound as an antiangiogenic and vasculature-disrupting agent that is far less toxic to normal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Wang at al. [ 25 ] reported that α-tomatine induced ER stress and triggered both caspase-dependent and caspase-independent apoptosis. Additionally, several authors recently reported a correlation between cellular stress response, translational reprogramming, and autophagy and apoptosis induction in the presence of a persistent upstream stress condition [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…α-tomatine, one of the main glycoalkaloids in tomato (Lycopersicon esculentum), has been reported to exert many beneficial effects, including biological, nutritional and pharmacological properties. Among the main activities of αtomatine, its immunological adjuvant action, antifungal and antibacterial activity, anticholesteremic effects, steroid hormone precursor status, anticancer potential, antimetastatic activity and cytostatic effect in various cancer cell lines are significant [11][12][13][14]19,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The α-tomatine content in mature tomatoes varies from 0.03-0.06 mg α-tomatine/100 g of fresh fruit [5][6][7][8][9]. α-tomatine possesses an important antifungal, antibacterial, antiviral, antimetastatic, cell membrane lysis, LDL cholesterol reducing, immunostimulatory, apoptosis and, most importantly, antiproliferative activity [7,[10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%